Evaluation of Anti-SARS-CoV-2 IgG antibody response following COVISHEILD vaccination: A comparison between previously infected and non-infected cohorts - Md Shakeel Ahmed; Md Zakir Hossain; Md Mamunur Rashid; Istiak Ahmad; Md Zahirul Islam; Meherab Hossain; Hasan Rabbi (Journal of Vaccines and Immunology - Peertechz Publications, 2023)
Background: The Coronavirus disease-2019 (COVID-19) pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a significant global health threat. In this study, we investigated the antibody response in five-time intervals following the COVISHEILD first, second, and booster doses vaccination in previously infected and previously non-infected individuals.  Methods: The study was a cross-sectional prospective study that took place at the Bangladesh Institute of Tropical and Infectious Diseases (BITID), Fouzderhat, Chittagong, in 46 individuals who received the COVISHEILD vaccine from February 2021 to January 2022. Blood samples were collected from vaccine recipients at five different time points (Baseline: Day 0 before 1st vaccine dose, 3 weeks, 2 months (before 2nd dose), 6 months, and 1 year after a booster dose) to measure the levels of S-RDB IgG antibodies using the EUROIMMUN Anti-S-Rose Disease Bioinfection assay test kits (Lübeck, Germany).  Results: The study reveals that individuals with prior SARS-CoV-2 infection showed a significant increase in antibody levels after receiving the first vaccine dose, reaching 145.51 units at 3 weeks post-vaccination. This response remained stable at 117.6 units at 3 months and slightly declined to 103.26 units at 6 months, indicating a sustained immune response. For previously non-infected individuals, vaccination induced a strong immune response, with antibody levels of 159.62 units at 3 weeks, increasing to 150 units at 3 months, and then slightly declining to 87.84 units at 6 months. Despite the decline, antibody levels at 6 months and 1 year were notably higher than the pre-vaccination baseline of 0 units, indicating the development of a durable immune response following vaccination. In the <40 years age group, individuals with prior SARS-CoV-2 infection showed a substantial boost in antibody levels after receiving the first vaccine dose, reaching 198.61 units at 3 weeks post-vaccination. The response remained stable at 122.22 units at 3 months and declined to 73.7 units at 6 months, followed by a rise to 263.85 units at 1 year.  Conclusion: Our findings highlight that tailoring vaccination approaches based on gender differences and considering vaccination in both previously and non-infected individuals will aid in optimizing immune responses and combatting the COVID-19 epidemic effectively.